School Management Model Based on Community Participation HARMONY Approach to Improving School Quality - Syahrial Syah; Dedy Achmad Kurniady; Tjutju Yuniarsih; Eka Prihatin; S. Supiani; N. Nurfitriah (FKIP Universitas Lampung, 2024)
School Management Model Based on Community Participation HARMONY Approach to Improving School Quality. Objective: This study aims to develop and implement a school management model based on community participation using the HARMONY approach to improve the quality of secondary schools in Kepulauan Meranti Regency. The research seeks to assess the effectiveness of this model in enhancing school quality through comprehensive community involvement. Methods: The research adopts a mixed-methods approach, combining both qualitative and quantitative data. Qualitative data were collected through in-depth interviews with the principal and vice principal of SMPN 1 Tebing Tinggi Barat and SMPN 2 Tebing Tinggi. Quantitative data were gathered through surveys involving various school stakeholders, such as teachers, students, and parents. Findings: The study’s results demonstrate that the implementation of a community participation-based school management model using the HARMONY approach significantly improves the quality of education in secondary schools in Kepulauan Meranti Regency. Data analysis reveals that effective school management has a significant impact on school quality, with a coefficient of 0.576. Community participation also shows a significant influence with a coefficient of 0.173. However, organizational culture does not significantly affect school quality and does not function as a strong mediator in the relationship between school management and community participation. Conclusion: The HARMONY approach standing for Holistic, Accountable, Responsive, Independent, Optimal, Normative, and Inclusive provides an innovative framework for integrating community participation into school management. This approach has the potential to enhance educational quality, especially in remote areas. The findings suggest that community-based school management is a viable solution for improving school performance in underdeveloped regions. Keywords: community participation, HARMONI approach, islands regency meranti, quality of education, school management.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202487